2014
DOI: 10.1007/s10815-014-0212-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in estrogen receptors (ESR1 and ESR2) with male infertility: a meta-analysis and systematic review

Abstract: This meta-analysis suggested that polymorphisms in the genes of ERs (ESR1 and ESR2) may have differential roles in the predisposition to male infertility according to the different ethnic backgrounds. Further well-designed and unbiased studies with larger sample size and diverse ethnic backgrounds should be conducted to verify our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Male infertility is an important problem and one of the causes of couples' inability to bear children (Ge et al, 2014[ 19 ]). It is estimated that there are about 30 million infertile men in the world (Agarwal et al, 2015[ 1 ]) and 15-30 % of causes of male infertility refer to genetic factors (Talebi et al, 2018[ 57 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male infertility is an important problem and one of the causes of couples' inability to bear children (Ge et al, 2014[ 19 ]). It is estimated that there are about 30 million infertile men in the world (Agarwal et al, 2015[ 1 ]) and 15-30 % of causes of male infertility refer to genetic factors (Talebi et al, 2018[ 57 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is a major health problem with associations to both genetic and environmental factors, affecting one-sixth of couples worldwide (Batiha et al, 2018[ 5 ]; Ge et al, 2014[ 19 ]). Approximately 50 % of infertility cases are attributed to male factors (Zorrilla and Yatsenko, 2013[ 67 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The gene product contains an N-terminal DNA-binding domain and a C-terminal ligand-binding domain and localizes to the nucleus, cytoplasm, and mitochondria [Lucas et al, 2008;Scariano et al, 2008;Tsezou et al, 2008]. ESR2 is one of the genes linked to spermatogenic failure and male infertility [Ge et al, 2014]. In addition, precocious puberty occurs in matUPD14 patients, which could result from an abnormality in ESR2 .…”
Section: Discussionmentioning
confidence: 99%
“…Ge et al. (2014) summarised the differential association of polymorphisms in oestrogen receptors ( PvuII, XbaI, RsaI and AluI ) with male infertility in their meta‐analysis and systematic review. Overall, it was found that the PvuII polymorphism in ESR1 was associated with significant decrease in the risk of male infertility.…”
Section: Hypothalamic–pituitary–gonadal/testicular Axismentioning
confidence: 99%
“…It can thus be inferred from the study of Ge et al. (2014) that polymorphisms of oestrogen receptor genes may have differential roles in the predisposition to male infertility according to the different ethnic background.…”
Section: Hypothalamic–pituitary–gonadal/testicular Axismentioning
confidence: 99%